Meta-analysis of the efficacy of lateral unicompartmental knee arthroplasty and total knee arthroplasty in the treatment of isolated lateral compartment knee osteoarthritis - Yong-le Wang; Yue Li; Jingle Zhuge; Xi-yong Li (Journal of Orthopaedic Surgery and Research)
Abstract Objectives To systematically evaluate the efficacy of lateral unicompartmental knee arthroplasty (LUKA) and total knee arthroplasty (TKA) in the treatment of isolated lateral compartment knee osteoarthritis (LCKO), and to provide guidance and a basis for selecting surgery in clinical practice. Methods Inclusion and exclusion criteria for literature were established, appropriate effect indicators were selected, and PubMed, Web of Science, Embase, Medline, Cochrane Library, and CNKI databases were searched using a computer. The Newcastle Ottawa scale (NOS) was used to evaluate the quality of the literature. After data extraction, Meta-analysis was performed using Revman5.4 software. Results A total of 8 studies were included in this meta-analysis, involving 490 patients, with 204 in the TKA group and 286 in the LUKA group. Meta-analysis found that, there was no significant statistical difference in operation time between the LUKA group and the TKA group. Nevertheless, LUKA offers advantages such as reduced intraoperative blood loss and shorter hospitalization time. At the same time, the LUKA group also had advantages over the TKA group in postoperative visual analogue scale (VAS) score, knee joint range of motion, Oxford Knee Score (OKS)score and Hospital for Special Surgery (HSS) score. Conclusion When LUKA and TKA are used to treat isolated LCKO, LUKA has the advantages of less intraoperative blood loss, shorter hospital stay, lower postoperative VAS score, and better knee function score and range of motion.